The Effect of Applying Active Learning Model Type Index Card Match on Students’ Higher Order Thinking Skills (HOTS) - Efni Cerya; Yulia Fitra (Universitas Negeri Semarang, 2023)
This study aims to determine the effect of applying active learning model type index card match on students’ higher order thinking skills. The type of this study is quasi-experimental research. The quasi-experimental design used was a nonequivalent control group design. The population in this study were all Class XI Social Sciences students at Public High School 2 Tilatang Kamang for the 2021/2022 academic year. Sampling in this study used simple random sampling technique of 52 respondents. The data analysis technique used Two-Way ANOVA with the SPSS version 22 program. The data collection method used test, questionnaires, and observation sheet. Based on the results of the research and data analysis, it can be concluded that the higher order thinking skills of students who are taught with the index card match learning model are significantly higher than those taught using the conventional learning model, the higher order thinking skills of students who have high learning activities is significantly higher than students who have low learning activities, and the index card match learning model and learning activities do not interact with each other in influencing students’ higher order thinking skills, which means that the two factors do not simultaneously exert their influence.